АНАЛІЗ ОПЕРАЦІЙ НАЦІОНАЛЬНОГО БАНКУ УКРАЇНИ НА ВІДКРИТОМУ РИНКУ - Лановий, Володимир Володимирович (Науковий журнал «Світ фінансів», 2017)
Лановий В. В. Аналіз операцій Національного банку України на відкритому ринку. Проаналізовано ефекти здійснення Національним банком України операцій на відкритому ринку з I кварталу 2010 року до І кварталу 2015 року. Запропоновано удосконалений підхід до аналізу обсягів здійснення операцій відкритого ринку, який ґрунтується на визначені середньоденного значення обсягів операцій Національного банку України на противагу абсолютним значенням обсягів операцій. За результатами дослідження встановлено місце цих операцій в інструментарії Національного банку України та визначено ефективність їх застосування при досягненні цілей монетарної політики. Лановой В. В. Анализ операций Национального банка Украины на открытом рынке. Изучены изменения к бюджетному законодательству Украины, которые внесены в части проведения реформы местного самоуправления и совершенствования его финансового обеспечения. Проанализирован зарубежный опыт мобилизации налога на прибыль предприятий в государственный и местные бюджеты, а также определены возможности его адаптации к отечественной практике. Рассмотрены неблагоприятные факторы налогообложения прибыли предприятий на местном уровне. Обоснованы теоретические и практические подходы к распределению этого налога между разными уровнями бюджетной системы. Lanovyi V. Analysis of operations of the National Bank of Ukraine on the open market. Introduction. By carrying out openmarket operations the National Bank of Ukraine directly affect the key indicators that characterize the banking system: its liquidity and interest rates. Purpose. According to the agreed with international financial institutions goals, for the purpose of reforming its activities, the National Bank of Ukraine took the responsibility to transfer to the regime that is based on price stability – inflation targeting in 2015.Methods. This article is to carry out analysis of the current trends in NBU’s openmarket operations for further estimation of their effectiveness and determination of main directions of their improvement.Results. According to the analysis’ results one can state that outright transactions with the government bonds continue to dominate among operational instruments of NBU’s monetary policy. It allowed the NBU to increase capital ratio of Ukrainian lending market and ensured money’s secure. In addition, since 2012, the amounts and maturities of the tender refinancing operations dramatically increased, which were in fact alternative to the central bank’s operations of bond purchase. For urgent purposes of current situation improvement NBU used large-scale mobilization operations. Such alternation of large amounts of refinancing and deposit operations caused destabilization of normal (market) resource allocation and balanced supply and demand for commercial loans.Conclusion. It can be noted that during the research Ukrainian central bank failed to achieve the main monetary policy objectives. In many cases it was the result of non-comprehensive approach when for specific non-market liquidity providing operations the balance of demand and supply on monetary assets was undermined and extensive interference in market processes were conducted.